Laporan teknikal pelan pengurusan pembangunan persisir pantai pekan Kuah-Klebang, Langkawi - Abdul Razak, Mohd. Zainal; Yahya, Mohammad Zaki; Asmawi, M. Zainora; Sapian, Abdul Razak; Mahamod, Lukman Hakim; Mohd Saad, Nor Shah (PLANMalaysia Pejabat Projek Zon Utara, 2019)
The technical report contains the sectors of landuse and physical, socio economy, transportation and infrastructure, environment and governance. Generally the report presents and addresses the present condition, analysis, findings and preliminary proposal of each sector.